A transient deep‐sea circulation switch during Eocene Thermal Maximum 2. (20th May 2014) - D'haenens, Simon; Bornemann, André; Claeys, Philippe; Röhl, Ursula; Steurbaut, Etienne; Speijer, Robert P.
Abstract Ever since its discovery, Eocene Thermal Maximum 2 (ETM2; ~53.7 Ma) has been considered as one of the "little brothers" of the Paleocene‐Eocene Thermal Maximum (PETM; ~56 Ma) as it displays similar characteristics including abrupt warming, ocean acidification, and biotic shifts. One of the remaining key questions is what effect these lesser climate perturbations had on ocean circulation and ventilation and, ultimately, biotic disruptions. Here we characterize ETM2 sections of the NE Atlantic (Deep Sea Drilling Project Sites 401 and 550) using multispecies benthic foraminiferal stable isotopes, grain size analysis, XRF core scanning, and carbonate content. The magnitude of the carbon isotope excursion (0.85–1.10‰) and bottom water warming (2–2.5°C) during ETM2 seems slightly smaller than in South Atlantic records. The comparison of the lateral δ13C gradient between the North and South Atlantic reveals that a transient circulation switch took place during ETM2, a similar pattern as observed for the PETM. New grain size and published faunal data support this hypothesis by indicating a reduction in deepwater current velocity. Following ETM2, we record a distinct intensification of bottom water currents influencing Atlantic carbonate accumulation and biotic communities, while a dramatic and persistent clay reduction hints at a weakening of the regional hydrological cycle. Our findings highlight the similarities and differences between the PETM and ETM2. Moreover, the heterogeneity of hyperthermal expression emphasizes the need to specifically characterize each hyperthermal event and its background conditions to minimalize artifacts in global climate and carbonate burial models for the early Paleogene.